Robust tori-like Lagrangian coherent structures - de Oliveira, Luis C.; Martins, Caroline G. L.; Roberto, M.; Caldas, I. L.; Egydio de Carvalho, R. [UNESP] (Elsevier B.V., 2012)
In general the term "Lagrangian coherent structure" (LCS) is used to make reference about structures whose properties are similar to a time-dependent analog of stable and unstable manifolds from a hyperbolic fixed point in Hamiltonian systems. Recently, the term LCS was used to describe a different type of structure, whose properties are similar to those of invariant tori in certain classes of two-dimensional incompressible flows. A new kind of LCS was obtained. It consists of barriers, called robust tori that block the trajectories in certain regions of the phase space. We used the Double-Gyre Flow system as the model. In this system, the robust tori play the role of a skeleton for the dynamics and block, horizontally, vortices that come from different parts of the phase space. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Robust tori; Lagrangian coherent structures; Double-gyre flow; Nonlinearities